2018
DOI: 10.1371/journal.pone.0203763
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of birth asphyxia among live birth newborns in University of Gondar referral hospital, northwest Ethiopia: A case-control study

Abstract: BackgroundBirth asphyxia, which accounts for 31.6% of all neonatal deaths, is one of the leading causes of such mortality in Ethiopia. Early recognition and management of its contributing factors would modify the problem. Thus, this study aimed to identify the determinants of birth asphyxia among live births at the University of Gondar Referral Hospital, northwest Ethiopia.MethodsA hospital-based unmatched case-control study was conducted from April to July 2017.Cases were newborn babies with an APGAR score of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
75
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(129 citation statements)
references
References 24 publications
(31 reference statements)
25
75
0
2
Order By: Relevance
“…This study is consistent with other previous studies conducted in India hospital, Pakistan in Karachi Tertiary Hospital, Phramongkutklao Hospital in Thailand, Nigeria Delta Tertiary Institute, Mulago Hospital in Uganda, Cameron Yaounde Tertiary Hospital, Gondar University Referral Hospital and Tigray Central Zone Public Hospitals in Ethiopia. 7,[11][12][13][14][15]17,19 The possible explanation could be that meconium-stained AF leads to peripartum inhalation of meconium-stained amniotic fluid, resulting in chemical pneumonitis including inflammation of the pulmonary tissue, mechanical narrowing of the airways and pulmonary air leakage, ending in hypoxia. 20 As for the presentation of neonates, those with nonvertex presentation show a significant association with neonatal birth asphyxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is consistent with other previous studies conducted in India hospital, Pakistan in Karachi Tertiary Hospital, Phramongkutklao Hospital in Thailand, Nigeria Delta Tertiary Institute, Mulago Hospital in Uganda, Cameron Yaounde Tertiary Hospital, Gondar University Referral Hospital and Tigray Central Zone Public Hospitals in Ethiopia. 7,[11][12][13][14][15]17,19 The possible explanation could be that meconium-stained AF leads to peripartum inhalation of meconium-stained amniotic fluid, resulting in chemical pneumonitis including inflammation of the pulmonary tissue, mechanical narrowing of the airways and pulmonary air leakage, ending in hypoxia. 20 As for the presentation of neonates, those with nonvertex presentation show a significant association with neonatal birth asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…Results: A total of 260 controls and 130 cases were enrolled in the study. Multivariable logistic regression showed that Primi-parity [AOR 5.5 (CI: 2.5,12.3)], pre-eclamcia/pregnancy-induced hypertension [AOR12.4 (CI: 4.17, 37.15)], post-term pregnancy [AOR 2.73 (CI: 1.00, 7.55)] meconium-stained liquor [AOR 29.2 (CI: 12.0, 71.1)], cord entangled [AOR 5.67 (CI: 1.66,19.3)] and non-vertex presentation [AOR 5.49 (CI: 2.20,13.7)] were found to be risk factors for perinatal birth asphyxia. Conclusion and Recommendations: Intrapartum factors and neonatal factors in the index pregnancy have an association with perinatal birth asphyxia.…”
mentioning
confidence: 99%
“…Six studies were included in this category of metaanalysis [13][14][15][16][17][18]. Neonates born with low birth weight were 6.52 times (OR: 6.52, 95% CI: 4.40, 9.65) more likely to develop perinatal asphyxia as compared to those born with normal weight.…”
Section: Determinants Of Perinatal Asphyxia Relationship Between Low mentioning
confidence: 99%
“…Studies from abroad indicated that low birth weight, caesarian section [10-12]; multiple births, lack of antenatal care[13]; maternal age, gravidity, mode of delivery [14], and prolonged labor, meconium stained amniotic fluid and fetal distress [12] were the significant causes of birth asphyxia. However, most of the studies were restricted in single institution and based on secondary data or records which may face to data/info incompleteness.…”
Section: Introductionmentioning
confidence: 99%